1999
DOI: 10.1063/1.869996
|View full text |Cite
|
Sign up to set email alerts
|

The effect of viscosity on the spherical stability of oscillating gas bubbles

Abstract: Gas bubbles driven in radial oscillations are subject to an instability of the spherical shape that is opposed by surface tension and viscosity. An exact linear formulation for the study of the phenomenon has been available for many years, but its complexity has discouraged a detailed investigation. With the recent theory of sonoluminescence of Lohse and co-workers [Hilgenfeldt et al., Phys. Fluids, 8, 2808 (1996)], there has been a renewed interest in the problem and new data have become available. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
86
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 30 publications
5
86
0
Order By: Relevance
“…These experimental and theoretical studies examine larger bubble sizes with smaller forcing pressures for which sonoluminescence cannot occur. Applying the above shape stability analysis in the regime P a ϳ0.5-1 atm Brenner et al, 1999;Hao and Prosperetti, 1999b;Augsdö rfer et al, 2000) gives similar thresholds to those found in experiment by Eller and Crum (1970), Horsburgh (1990), and Gaitan and Holt (1998). For P a Շ0.9 atm, the nϭ3 mode takes over as the most unstable surface mode from the nϭ2 mode Brenner et al, 1999;Augsdö rfer et al, 2000), just as was found in the experiments by Gaitan and Holt (1998).…”
Section: Parametric Instabilitysupporting
confidence: 67%
See 4 more Smart Citations
“…These experimental and theoretical studies examine larger bubble sizes with smaller forcing pressures for which sonoluminescence cannot occur. Applying the above shape stability analysis in the regime P a ϳ0.5-1 atm Brenner et al, 1999;Hao and Prosperetti, 1999b;Augsdö rfer et al, 2000) gives similar thresholds to those found in experiment by Eller and Crum (1970), Horsburgh (1990), and Gaitan and Holt (1998). For P a Շ0.9 atm, the nϭ3 mode takes over as the most unstable surface mode from the nϭ2 mode Brenner et al, 1999;Augsdö rfer et al, 2000), just as was found in the experiments by Gaitan and Holt (1998).…”
Section: Parametric Instabilitysupporting
confidence: 67%
“…Holt and Gaitan (1996;Gaitan and Holt, 1999) also measured shape instabilities in the sonoluminescence regime and close to it. Their experimental results were compared with theory in the work of Brenner, Dupont, et al (1998) and Hao and Prosperetti (1999b), with good agreement in evidence [see Fig. 35(a)].…”
Section: Parametric Instabilitymentioning
confidence: 99%
See 3 more Smart Citations